2022
DOI: 10.1186/s12885-022-09465-9
|View full text |Cite
|
Sign up to set email alerts
|

A new nomogram model for prognosis of hepatocellular carcinoma based on novel gene signature that regulates cross-talk between immune and tumor cells

Abstract: Background The combined application of immune cells and specific biomarkers related to the tumor immune microenvironment has a better predictive value for the prognosis of HCC. The purpose of this study is to construct a new prognostic model based on immune-related genes that regulate cross-talk between immune and tumor cells to assess the prognosis and explore possible mechanisms. Method The immune cell abundance ratio of 424 cases in the TCGA-LIH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…found that SPP1 expression was tightly linked to the TME reprogramming and tumor progression in response to therapy by single-cell transcriptomic analysis ( 67 ). S100A9, PLXNA1, and EPO were also reported as candidates for HCC prognostic signatures, implying their subtle effects on the disease progression of HCC patients ( 68 70 ). Moreover, BIRC5 was also found to be highly expressed in liver cancer ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that SPP1 expression was tightly linked to the TME reprogramming and tumor progression in response to therapy by single-cell transcriptomic analysis ( 67 ). S100A9, PLXNA1, and EPO were also reported as candidates for HCC prognostic signatures, implying their subtle effects on the disease progression of HCC patients ( 68 70 ). Moreover, BIRC5 was also found to be highly expressed in liver cancer ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that inflammation-associated genes risk signature can be used to predict patient prognosis and guide treatment for esophageal squamous cell carcinoma, lung adenocarcinoma and urothelial bladder cancer. [28][29][30][31] Other hand, Sia et al determined that inflammation response-related gene signature could be correlated with the immune exhausted. 32 Many cancers are characterized by simultaneous immunosuppression and inflammation, their regulation is integrally linked, which can induce a dysfunctional immune state unable to eliminate disease.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 905,677 million cases were estimated to be first diagnosed with HCC, and this disease caused 830,180 deaths in 2020 globally, ranking for approximately 4.7% of newly diagnosed cancer cases and 8.3% of cancer-related deaths [ 2 ]. Characterized by a high rate of invasiveness, recurrence and metastasis, the prognosis of HCC is poor, and the 5-year overall survival (OS) is only approximately 30% [ 3 ]. Although some risk factors have been identified for HCC, including HBV infection and alcohol consumption, the molecular mechanism of HCC is far from being elucidated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%